2021
DOI: 10.3390/ma14227013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Impact of Glass Beads on Adhesive Joint Strength and Its Failure Mechanism

Abstract: The use of modern structural adhesives provides a lightweight, practical, and high strength joining methodology, which is increasingly being adopted in the automotive and aeronautical sectors, among many others. However, the strict mechanical performance standards that must be met in these applications require a constant search for ways of improving the adhesives’ behavior, which has led to the growing use of reinforcements as a way of improving the capabilities of bonded joints. The aim of this work was, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…With regard to the fracture toughness, similar to what was reported in the work of Forte et al [ 17 ] regarding the influence of fiber-glass fibers in the adhesive layer, there is an overall decrease of the critical energy release rate in mode-I. This behavior translates into a decreasing capability of the adhesive to absorb energy as the amount of glass particles increases, resulting in the conclusion that this filler does not work as a toughening mechanism.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…With regard to the fracture toughness, similar to what was reported in the work of Forte et al [ 17 ] regarding the influence of fiber-glass fibers in the adhesive layer, there is an overall decrease of the critical energy release rate in mode-I. This behavior translates into a decreasing capability of the adhesive to absorb energy as the amount of glass particles increases, resulting in the conclusion that this filler does not work as a toughening mechanism.…”
Section: Resultssupporting
confidence: 77%
“…The manufacturing plan followed two main premises: the %v/v’s used in a previous study on SLJ failure mechanisms [ 17 ], as well as the need for a reference and a benchmark subject for the study on the validity of property prediction through ROM. As such, the study was divided into an extensive characterization of Adhesive A with small 5%v/v GB increments from 0% to 15%, used as the reference data sample and a less considerable one for Adhesive B with two different configurations at 0% and 10%, as the benchmark data sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The joints were tested in aged and unaged conditions. The results showed an improvement in the area of cohesive failure with a negligible effect on joint strength, similar to Santos et al [18]. Aradhana et al [20] used a combination of reduced graphite oxide (rGO) and silica hollow microspheres (SiHM) to produce a filler mixture that improved the conductivity of an epoxy adhesive.…”
Section: Introductionsupporting
confidence: 73%
“…In a similar effort, Santos et al [18] showed that the addition of 5% to 15% v/v of hollow glass beads to a 1K epoxy adhesive progressively changed the failure of mild steel adhesive single lap joint (SLJ) specimens from mixed, where half of the fracture surface was adhesive failure, to fully cohesive failure in the adhesive. Bruckner et al [19] also researched the use of hollow glass microspheres on a 1K epoxy adhesive via SLJ specimens.…”
Section: Introductionmentioning
confidence: 99%